10-year follow-up study on attendance pattern after dental treatment in primary oral health care clinic for fearful patients - Taina Kankaala; Heikki Laine; Marja-Liisa Laitala; Päivi Rajavaara; Hannu Vähänikkilä; Paula Pesonen; Vuokko Anttonen (BMC, 2021)
Abstract Background Dental fear may lead to avoidance of regular dental treatment. The scope of this long-term practe-based study was to monitor the dental attendance of patients who received chair-side dental and fear treatment. Methods In 2000-2006, patients in the City of Oulu, Finland, received treatment for dental fear in the Clinic for Fearful Dental Patients (CFDP) from primary health care dentists trained on this subject. Of the originally treated patients (n = 163), 152 (93%) with sufficient information in dental records made up the study population. Information on their age and sex was available. The number of dental examinations, emergency visits and missed appointments was collected covering the follow-up period of 10 years 2006-2016. For analyses, data were dichotomized according to age at baseline and preliminary outcome baseline condition of dental fear treatment evaluated in 2006. To investigate association further, Poisson regression as well as binary logistic regression models were conducted. As register keeper, the City of Oulu gave permission for this retrospective data-based study. Results Patients receiving dental fear treatment at younger age (2-10 y) had significantly more dental examinations than those treated at > 10 years. Preliminary success was associated with the number of examinations, but not with emergency visits and missed appointments. Sex was not a significant factor in later dental attendance. There was an association between few dental examinations and dental emergency care need with unsuccessful baseline outcome of dental fear treatment. Conclusions Successful dental fear treatment especially at an early age is beneficial for future dental attendance measured by the number of examinations and consequently, less need for emergency care than in the opposite case. Successful fear treatment has positive impact on later dental care and regular dental attendance.